Strategies For Overloaded Employees: Leveraging Resilience And Forgiveness To Mitigate Dissatisfaction And Sustain Knowledge-Sharing Efforts Mediating Role Of Psychological Well-Being - Dr. Ana Atta , Dr Liaqat Ali (Migration Letters, 2024)
The study explored how resilience and forgiveness, as organisational strategies, can enhance psychological well-being among overloaded employees, thereby reducing dissatisfaction and sustaining knowledge-sharing efforts. It also investigates how psychological well-being mediates the relationship between these strategies and the sustainability of knowledge-sharing efforts. The data was collected from 250 employees of Pakistani service sector firms. The data was analysed using Smart PLS which involved conducting a Confirmatory Factor Analysis (CFA[1]) to validate the measurement model. The study found that organisational forgiveness (β = 0.2662, p = 0.0003) improves employees’ psychological well-being and indirectly boosts knowledge sharing efforts (β = 0.2105, p = 0.0005). Psychological well-being significantly mediated organisational forgiveness and knowledge sharing (β = 0.7906, p < 0.001). It further revealed no significant impact of resilience on job dissatisfaction (β = -0.1035, p = 0.2633) and knowledge sharing (β = -0.443, p = 0.3157). The results showed that provoking workplace culture improves employee well-being and knowledge sharing. According to research, when employees are frustrated due to job demands, they share less information and are less likely to obtain helpful feedback for addressing issues.